2015
DOI: 10.1080/01900692.2015.1001239
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing Private or Public Accountability in the Public Sector? Applying IPSASs to Define the Reporting Entity in Municipal Consolidation

Abstract: Private-sector accounting systems have often been heralded as superior to public-sector ones and suggested as solutions to the shortcomings of the latter. Our article aims at contributing to this debate by looking at the adoption of business-like practices where the public and private sectors intersect. Our analysis shows that the adoption of International Public Sector Accounting Standards (IPSASs), strongly inspired by International Financial Reporting Standards (IFRS), might not ensure the expected disclosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 62 publications
0
46
0
4
Order By: Relevance
“…Consolidation for subsectors Consolidations for subsectors should precede any whole-of-government consolidation 1 on communities; Grossi & Steccolini, 2014) suggest taking into account both financial and non-financial performance, which in turn are affected by many different activities, functions, and services (Boyne, 2002), because profit should not be assumed as "the" goal of a PSE (Cohen, Doumpos, Neofytou, & Zopounidis, 2012;Guthrie, 1998;Guthrie & Johnson, 1994;Farnham & Horton, 1996, p. 31;Ma & Matthews, 1993).…”
Section: Exclusion From Consolidation Of Controlled Entitiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Consolidation for subsectors Consolidations for subsectors should precede any whole-of-government consolidation 1 on communities; Grossi & Steccolini, 2014) suggest taking into account both financial and non-financial performance, which in turn are affected by many different activities, functions, and services (Boyne, 2002), because profit should not be assumed as "the" goal of a PSE (Cohen, Doumpos, Neofytou, & Zopounidis, 2012;Guthrie, 1998;Guthrie & Johnson, 1994;Farnham & Horton, 1996, p. 31;Ma & Matthews, 1993).…”
Section: Exclusion From Consolidation Of Controlled Entitiesmentioning
confidence: 96%
“…In other words, the main problematic issue is the definition of appropriate criteria concerning the consolidation area (Heald & Georgiou, 2000;Robb & Newberry, 2007;Tagesson, 2009;Walker, 2009), whose solution should not be simplistically based on the criteria used in the private sector (Grossi & Steccolini, 2014). In fact, the consolidation area concerning PSEs can be identified in accordance with different criteria, which lead to different approaches (Bergman, 2009).…”
Section: Consolidation Theories and Approachesmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the adoption of a set of principles, recognized worldwide, inevitably gives greater credibility in the eyes of other nations. Also, some politicians believe that the adoption of international standards would legitimise the financial reports, but various studies have shown that this is not necessarily true (Grossi & Steccolini, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Other works found that the lack of homogeneity was higher among European countries (Benito et al, 2007). We could say that some of the reasons for this difference is that continental European countries have a strong legal-code tradition and a long-stand tradition on budgetary and cash accounting (Grossi & Steccolini, 2015). Therefore, difficulties in the implementation of IPSAS and the heterogeneity of the European context led to creation of regional accounting standards (EPSAS); although based on IPSAS (Caperchione, 2015).…”
Section: Box 1 Governmental Accounting Practicesmentioning
confidence: 99%